Face milling of Inconel 625 via wiper inserts: Evaluation of tool life and workpiece surface integrity. (August 2020) - Saleem, Muhammad Qaiser; Mumtaz, Salman
Highlights: Axial DOC contributes most for wiper inserts' tool life while machining Inconel 625. Adhesion, BUE, attrition and chipping are the main wear mechanisms at low axial DOC. Wiper inserts' feed/tooth contributes most for surface roughness of Inconel 625. An extended work-hardened subsurface layer is seen for max. tool life condition. Abstract: Ni-based superalloy Inconel 625, despite its extensive applications (in aerospace, oil and gas, marine, chemical processing and alike industry) is categorized as difficult-to-cut material due to distinct thermal and physical characteristics. Incidentally, the use of novel multi radii insert (wiper) geometry, that is reported to provide extended machining capabilities for different materials and machining scenarios has not been found to be reported for this alloy. This work employs PVD coated carbide inserts with novel wiper edge geometry for face milling of Inconel 625 under dry cutting conditions. Cutting speed, feed per tooth and axial depth of cut have been taken as input variables and machining performance is evaluated in terms of tool life, tool wear analysis, material removed and surface integrity aspects (namely roughness and microhardness). Taguchi L8 array has been employed for experimentation phase followed by post experimental analysis. It is found that for tool life, axial depth of cut is the most significant factor with contribution of 45.43%. Maximum tool life of 42.8 min was achieved when machining was done employing lower values of feed (0.08 mm/tooth) and axial depth of cut (0.25 mm) with higher value of cutting speed (45 m/min). For the case of surface roughness, feed/tooth is found to be the most contributing factor (PCR 46.25%). Results are found to be correlating well with the cutting temperatures generated during the process. Experiments with minimum axial depth of cuts resulted in lesser temperatures and better output parameters in general. Review of the wear pattern via SEM analysis indicate adhesion, BUE, attrition and chipping to be the main wear mechanism in general except where higher axial depth of cut (0.5 mm) was employed that culminated in fracture. For the conditions where maximum tool life was obtained, a work-hardened layer was observed beneath the machined surface extending up to ∼400 μm depth. An indirect comparison of the results with other literature reported face milling scenarios of Inconel 625 (where other tool types are employed), seems to indicate the effectiveness of wiper inserts employed herein. The results are well explained and supported by the physical phenomenon involved.